1997
DOI: 10.1104/pp.115.2.437
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Sesquiterpene Cyclase Gene Expression (Characterization of an Elicitor- and Pathogen-Inducible Promoter)

Abstract: The promoter for a tobacco (Nicofiana tabacum) sesquiterpene cyclase gene, a key regulatory step in sesquiterpene phytoalexin biosynthesis, has been analyzed. The EAS4 promoter was fused to the P-glucuronidase (CUS) reporter gene, and the temporal and spatial expression patterns of C U S activity were examined in stably transformed plants and in transient expression assays using electroporated protoplasts of tobacco. N o C U S activity was observed i n any tissues under normal growth conditions. A low level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 80 publications
6
51
0
Order By: Relevance
“…MJ elicitation has also been implicated in the activation of the defense related leucine aminopeptidase promoter in Nicotiana, the strictosidine synthase promoter in Catharanthus, and a sesquiterpene synthase promoter in Nicotiana are activated with MJ elicitation (17,36,40). In this investigation, we have shown that five paclitaxel biosynthetic pathway gene promoters are likewise activated by MJ elicitation.…”
Section: Withdrawn At Authors Requestmentioning
confidence: 61%
“…MJ elicitation has also been implicated in the activation of the defense related leucine aminopeptidase promoter in Nicotiana, the strictosidine synthase promoter in Catharanthus, and a sesquiterpene synthase promoter in Nicotiana are activated with MJ elicitation (17,36,40). In this investigation, we have shown that five paclitaxel biosynthetic pathway gene promoters are likewise activated by MJ elicitation.…”
Section: Withdrawn At Authors Requestmentioning
confidence: 61%
“…In tobacco, formation of sesquiterpenoid phytoalexins is also catalyzed by multiple isozymes of EAS, and the tobacco genome is believed to contain 12-15 copies EAS genes. 15,16 Total RNAs were isolated from seeds of a glanded cotton cultivar G. hirsutum cv. Sumian-6, at four intervals ranging from 20, 27, 35, to 40 days postanthesis (DPA), approximately corresponding to stages of embryogenensis of the later cotyledon, early maturation, mid-maturation, and late maturation.…”
Section: Resultsmentioning
confidence: 99%
“…14 In G. arboreum cell suspension cultures, mRNA levels of both cad1-C and cad1-A subfamilies were increased by 10 times at 6-10 h posttreatment with V. dahliae cellular extracts, followed by increased levels of cyclase proteins. 11,12 Similarly, the expression of genes of a number of other plant terpene cyclases, such as tobacco 5-epi-aristolochene synthase (EAS), 15,16 Hyoscyamus muticus vetispiradiene synthase, 17 and Ricinus communis casbene synthase, 18 was induced in cell cultures or plant tissues by elicitation.Formation of pigment glands and their sesquiterpene content is genetically and developmentally controlled in cotton species but appears not to be related to environmental stimuli. 19 In developing cottonseeds, the young cotyledons are well protected by the seed-coat.…”
mentioning
confidence: 99%
“…The coordinated responses suggest that GaWRKY1 and CAD1-A are components of the same pathway of cotton defense reaction, which involves induced biosynthesis of sesquiterpene phytoalexins. Searching of databases revealed the presence of W-box elements in the promoter region of sesquiterpene cyclase genes of other plants, such as 5-epi-aristolochene synthase gene EAS4 of tobacco (Yin et al, 1997), putative sesquiterpene cyclase genes of Arabidopsis (At1g31950), and rice (Oryza sativa; BAC99543.1). Therefore, WRKY-W-box interactions are likely operating also in other plants in regulation of sesquiterpene biosynthesis.…”
Section: Discussionmentioning
confidence: 99%